Implementation of a decentralized community-based treatment program to improve the management of Buruli ulcer in the Ouinhi district of Benin, West Africa. - Arnaud Setondji Amoussouhoui; Ghislain Emmanuel Sopoh; Anita Carolle Wadagni; Roch Christian Johnson; Paulin Aoulou; Inès Elvire Agbo; Jean-Gabin Houezo; Micah Boyer; Mark Nichter (Public Library of Science (PLoS), 2018)
Mycobacterium ulcerans infection, commonly known as Buruli ulcer (BU), is a debilitating neglected tropical disease. Its management remains complex and has three main components: antibiotic treatment combining rifampicin and streptomycin for 56 days, wound dressings and skin grafts for large ulcerations, and physical therapy to prevent functional limitations after care. In Benin, BU patient care is being integrated into the government health system. In this paper, we report on an innovative pilot program designed to introduce BU decentralization in Ouinhi district, one of Benin's most endemic districts previously served by centralized hospital-based care.We conducted intervention-oriented research implemented in four steps: baseline study, training of health district clinical staff, outreach education, outcome and impact assessments. Study results demonstrated that early BU lesions (71% of all detected cases) could be treated in the community following outreach education, and that most of the afflicted were willing to accept decentralized treatment. Ninety-three percent were successfully treated with antibiotics alone. The impact evaluation found that community confidence in decentralized BU care was greatly enhanced by clinic staff who came to be seen as having expertise in the care of most chronic wounds.This study documents a successful BU outreach and decentralized care program reaching early BU cases not previously treated by a proactive centralized BU program. The pilot program further demonstrates the added value of integrated wound management for NTD control.